Utilization of Carbonized Wood from Tropical Fast-Growing Trees for Functional Materials - Joko Sulistyo; Toshimitsu Hata; Sri Nugroho Marsoem (Jurnal Ilmu Kehutanan, 2012)
Pembangunan hutan tanaman dari jenis-jenis cepat tumbuh di kawasan tropis menimbulkan limbah biomassa kayu yang sebagian saat ini digunakan untuk kayu bakar dan sebagian lain digunakan untuk produksi arang dengan tujuan penggunaan yang terbatas. Pengembangan material-material fungsional untuk berbagai aplikasi teknik dengan memanfaatkan arang kayu dari jenis pohon cepat tumbuh harus mempertimbangkan struktur mikro dan struktur pori dalam arang kayu yang berhubungan dengan kondisi karbonisasi. Ulasan ini meliputi kemajuan penelitian-penelitian saat ini pada karbonisasi kayu dari pohon cepat tumbuh tropis, mekanisme perkembangan struktur mikro dan struktur pori dalam arang kayu selama karbonisasi, pemanfaatan yang tepat dari struktur mikro dan porositas dalam arang kayu untuk pengembangan material-material fungsional serta usaha dan peningkatan pengembangan material-material fungsional menggunakan arang kayu dari pohon cepat tumbuh tropis.Katakunci: arang kayu, material fungsional, pohon cepat tumbuh, karbonisasi Utilization of Carbonized Wood from Tropical Fast-Growing Trees for Functional MaterialsAbstractEstablishment of fast-growing tree species plantations in tropical areas generate wood biomass residue in which some of them are currently utilized for heating fuel and some others are used for charcoal production with limited purposes. The development of functional materials for engineering applications utilizing carbonized wood from fast-growing trees species have to consider the microstructure and pore structure in carbonized wood which has a relationship to the carbonization conditions. This review covers the current researches on progress in the carbonization of wood from tropical fast-growing trees, mechanism of the microstructure and pore structure development in carbonized wood during carbonization, proper utilizations of the microstructure and porosity in carbonized wood for the development of functional materials and efforts and enhancing the development of functional materials using carbonized wood from tropical fast-growing trees.